2003
DOI: 10.1002/jcb.10469
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer gene 1 (BRCA1): Role in cell cycle regulation and DNA repair—perhaps through transcription

Abstract: Mutations of BRCA1 gene are associated with more than half the cases of hereditary breast cancer. Breast cancer formation in BRCA1 mutation carriers is generally accompanied by loss of the wild-type allele, suggesting that BRCA1 protein may function as a tumor suppressor. The human BRCA1 gene encodes a nuclear protein of 1863 amino acids. Although several lines of evidences suggest that BRCA1 protein may have a role to play in cell cycle regulation, DNA repair, and other processes, the exact mechanism of funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 61 publications
1
47
0
Order By: Relevance
“…How does this translate to the biology of breast cancer cells? Not surprisingly, several ERα corepressors (such as SAFB1 and BRCA1) are able to block cell cycle progression (Townson et al 2000, Venkitaraman 2002, Somasundaram 2003. Also, SAFB1 overexpression significantly inhibits both anchorage-dependent and -independent growth of breast cancer cell lines (Townson et al 2000 and Oesterreich et al, unpublished results).…”
Section: Er␣ Corepressors and Breast Cancer -Results From Cell Line Amentioning
confidence: 99%
“…How does this translate to the biology of breast cancer cells? Not surprisingly, several ERα corepressors (such as SAFB1 and BRCA1) are able to block cell cycle progression (Townson et al 2000, Venkitaraman 2002, Somasundaram 2003. Also, SAFB1 overexpression significantly inhibits both anchorage-dependent and -independent growth of breast cancer cell lines (Townson et al 2000 and Oesterreich et al, unpublished results).…”
Section: Er␣ Corepressors and Breast Cancer -Results From Cell Line Amentioning
confidence: 99%
“…But it is considered that mutation in the BRCA1 and BRCA2 genes profoundly increase the risk of developing breast and/or ovarian cancer among women. Although their mechanism of action is not yet fully elucidated it is assumed that these genes play a key role in important cellular pathways including response to DNA damage, transcription, and interaction with other proteins involved in DNA repair and apoptosis [15][16]. This study revealed that PCR amplification that was carried out by using specific 141 primers (BRCA1 and BRCA2) are shown positive in case of breast cancer and shown negative in control sample (Fig-2).…”
Section: Discussion:-mentioning
confidence: 74%
“…On the other hand, Hung, et al [34] reported that EMR exposure did not produce significant changes in cell numbers, cell cycle distribution, or level of DNA damage or global gene expression. The mutation in BRCAI gene leads to multiple genetic alterations including the inactivation of TP53 gene and activation of a number of oncogenes as reported by Somasundaram [35]. Whereas mutations in TP53 seem to occur at a very high frequency in BRCAI mutation, suggesting that P53 might be an important checkpoint for BRCAI associated tumorigenesis [36].…”
Section: Discussionmentioning
confidence: 89%